2022
DOI: 10.1371/journal.pone.0268675
|View full text |Cite
|
Sign up to set email alerts
|

Researchers’ perspective of real-world impact from UK public health research: A qualitative study

Abstract: Research funded by the National Institute for Health Research Public Health Research Programme is being undertaken in a complex system which brings opportunities and challenges for researchers to maximise the impact of their research. This study seeks to better understand the facilitators, challenges and barriers to research impact and knowledge mobilisation from the perspective of UK public health researchers. A qualitative study using semi-structured interviews, informed by the Payback Framework, with public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…There is consensus that if knowledge is shared between two or more communities, it can result in the creation of new knowledge, which has a greater likelihood of leading to change within practice or research [ 7 , 19 21 ]. Change that can be linked back to original research findings or outcomes is often referred to as research impact [ 22 – 24 ]. Techniques and approaches that have been developed to follow this mechanism of knowledge sharing include, models of embedded researchers or practitioners, use of knowledge brokers, stakeholder engagement, organisational collaborative partnerships and the involvement of stakeholders in the research or service design process itself.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is consensus that if knowledge is shared between two or more communities, it can result in the creation of new knowledge, which has a greater likelihood of leading to change within practice or research [ 7 , 19 21 ]. Change that can be linked back to original research findings or outcomes is often referred to as research impact [ 22 – 24 ]. Techniques and approaches that have been developed to follow this mechanism of knowledge sharing include, models of embedded researchers or practitioners, use of knowledge brokers, stakeholder engagement, organisational collaborative partnerships and the involvement of stakeholders in the research or service design process itself.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the standardised measures were not capturing impact in localised settings or longer-term impact [ 23 ]. A second study explored the public health researchers’ perspectives on impact reporting and highlighted a need for funders to identify their expectations of the impact resulting from the research they fund and to increase their support for knowledge mobilisation activities [ 24 ]. These studies highlighted the need for researchers to have a clearer understanding of the knowledge mobilisation techniques and approaches to inform pathways to impact and focused on NIHR health funding streams [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation